2014
DOI: 10.1002/pmic.201300427
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics and metallomics studies in Arabidopsis thaliana leaf tissues: Evaluation of the selenium addition in transgenic and nontransgenic plants using two‐dimensional difference gel electrophoresis and laser ablation imaging

Abstract: The main goal of this work is to evaluate some differential protein species in transgenic (T) and nontransgenic (NT) Arabidopsis thaliana plants after their cultivation in the presence or absence of sodium selenite. The transgenic line was obtained through insertion of CaMV 35S controlling nptII gene. Comparative proteomics through 2D-DIGE is carried out in four different groups (NT × T; NT × Se-NT (where Se is selenium); Se-NT × Se-T, and T × Se-T). Although no differential proteins are achieved in the T × Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
13

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 32 publications
0
16
0
13
Order By: Relevance
“…Finally, purified peptides were eluted from the resin using 20 ll of 0.1% (v/v) TFA in 50% (v/v) acetonitrile solution. For vacuum-elution, a Multiscreen Ò Vacuum Manifold (Millipore) was used (Maciel et al, 2014).…”
Section: Trypsin Digestion Of Peptidesmentioning
confidence: 99%
“…Finally, purified peptides were eluted from the resin using 20 ll of 0.1% (v/v) TFA in 50% (v/v) acetonitrile solution. For vacuum-elution, a Multiscreen Ò Vacuum Manifold (Millipore) was used (Maciel et al, 2014).…”
Section: Trypsin Digestion Of Peptidesmentioning
confidence: 99%
“…14, Issues 7-8), in which two plant studies were reported. Maciel et al [24] used the laser ablation imaging technique to evaluate the distribution of selenium and sulfur in leaves of transgenic and nontransgenic A. thaliana. One of the limitations of imaging studies is the processing of high amounts of datasets, and therefore attention has been given to data processing methods, as discussed by Wijetunge et al [63] and Franceschi and Wehrens [64].…”
Section: Wet and Dry Methodologies 21 In Vitro And In Situ Proteomicmentioning
confidence: 99%
“…15, Issues 5-6 (Reviews 2015) and 10 (Plant-based Foods: Seed, Nutrition, and Human Health). Strikingly, the thematic issues covering the most recent technical novelties or the frontier in proteomics and biology knowledge have none or at most two plant papers per issue; it was the case of Tissue Proteomics and Imaging Mass Spectrometry (Vol.14, Issues 7-8, one plant reference by Maciel et al [24]) and OMICS Views on Protein N-terminal Biology (Vol. 15, Issue 4, two plant original papers by Zhang et al [25] and Venne et al [26]).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the rapid progress in the determination, quanti cation, identi cation and comprehension of proteins has been possible due to the use of model organisms such as A. thaliana. Improvements in the techniques for proteomics, including plant proteomics, based on existing platforms such as 2-DE, 2-LC and MS and some new techniques, including tandem a nity and protein chips, have been observed [38][39][40][41][42][43][44][45][46][47]. e availability of the entire genomic sequence of A. thaliana provides unique opportunities for the use of a postgenomic tool such as proteomics in its full capacity [11,[17][18][19][20][21][22]48,49].…”
Section: Proteomics Studiesmentioning
confidence: 99%